Preparation and characterization of cation exchange resins based on locally fabricated polythylene pallets - Nasef, Mohamed Mahmoud (Faculty of Chemical and Natural Resource Engineering, 2009)
The objective of the present project was to prepare and characterize cation exchange resins based locally fabricated low density polyethylene (LDPE) using radiation induced grafting method. The resins denoted as LDPE-g-PSSA were prepared by radiation induced grafting of styrene monomer onto LDPE particles followed by sulfonation reaction to introduce sulfonic acid moiety. The effect of various reaction parameters such as monomer concentration, irradiation dose, diluting solvent addition of inhibitor and addition of acid on the degree of grafting of the resins were investigated. The degree of grafting was found be heavily dependent upon the investigated parameters in a way that led to a close control over the composition of the resins. The introduction of polystyrene to LDPE resins and subsequent sulfonation was confirmed by FTIR spectral analysis. The water uptake and the ion exchange capacity of the obtained resins were evaluated. The thermal properties, thermal stability and mechanical stability of the obtained cation exchange resins were also studied using differential scanning calorimetry (DSC), thermal gravimetric analysis (TGA), respectively. X-ray diffraction was also used to determine the structural changes took place in LDPE in correlation with the two-step procedure i.e. grafting and sulfonation and variation of the degree of grafting. The physical and chemical properties of the obtained resins we found to be strongly dependent on the degree of grafting. The obtained resins were found to have very good combination of properties compared to corresponding commercial sulfonated resins. It can be concluded that radiation grafted LDPE-g-PSSA resins have potential to be applied in water and waste water treatment. Moreover, radiation induced grafting is a convenient method to cation exchange resins.